Galectin-3 and Cardiovascular Biomarkers Reflect Adaptation Response to Scuba Diving - Žarak, Marko; Perović, Antonija; Dobrović, Irena; Goreta, Sandra Šupraha; Dumić, Jerka (International Journal of Sports Medicine, 2020)
To understand better the adaptation response of the cardiovascular system (CVS) to self-contained underwater breathing apparatus (SCUBA) diving, Galectin-3 (Gal-3) and specific CVS biomarkers were measured in plasma of 16 male recreational divers before and after (30 min, 3 and 6 h) diving (total time of 30 min at 30 m depth) undertaken a after long non-dive period. The one-time SCUBA dive caused a significant increase in Gal-3, N-terminal prohormone of brain natriuretic peptide (NT-proBNP), high-sensitivity troponin-I (hs-TnI), and myoglobin immediately after diving. Whereas Gal-3 and myoglobin dropped down to the basal levels during the recovery period, NT-proBNP and hs-TnI concentration continued to increase. An immediate increase of vascular endothelial growth factor, detected immediately after diving, was followed by a significant decrease and return to the basal level, 3 and 6 h after diving, respectively. After a significant initial decrease, endothelin-1 increased during the recovery period, but did not return to the basal level. The observed changes in these biomarkers reflect comprehensive, but transient adaptation of CVS and muscular system to the specific environmental conditions during the SCUBA dive. Whether the recurrent activation of these adaption mechanisms due to repetitive dives has positive or negative effects on CVS remains to be elucidated.
Keywords: SCUBA diving; galectin-3; cardiovascular biomarkers; myoglobin